Physicochemical and antibacterial characteristics of methylcellulose and sodium caseinate films containing lactic acid bacteria - Hoda Ghayoomi; MohammadAli Najafi; Nasrin Hadinia (Applied Food Research)
A new approach to developing functional food is the use of edible films containing lactic acid bacteria. In this study, films of methylcellulose, sodium caseinate, Lactobacillus casei, and Lactobacillus rhamnosus (106 CFU/cm2) were evaluated by physical, chemical, SEM, antimicrobial, and viability assays. In comparison to the control film, films containing lactic acid bacteria showed higher moisture content, water solubility, water vapor permeability, and elasticity, but lower tensile strength and elastic modulus (p < 0.05). The presence of lactic acid bacteria also significantly changed the films' color parameters (p < 0.05). After drying the film, the viability of lactic acid bacteria decreased. The survival rate of lactic acid bacteria at 4 °C and 25 °C during storage for one month was as follows: Lactobacillus casei in sodium caseinate film (4.50–5.14) < Lactobacillus casei in methylcellulose film (3.80–4.34) < Lactobacillus rhamnosus in sodium caseinate film (3.24–4.10) < Lactobacillus rhamnosus in methylcellulose film (2.47–3.33). Films containing lactic acid bacteria significantly inhibited Pseudomonas aeruginosa and Listeria innocua (p < 0.05). The best results were achieved with sodium caseinate film containing Lactobacillus casei, which maintained its original properties with no significant changes. These films exhibited the highest survival rates for Lactobacillus casei and demonstrated the most effective inhibition against Listeria innocua and Pseudomonas aeruginosa (3 and 4.45) (p < 0.05). As a result, these films can be used as carriers for lactic acid bacteria to generate bioactive films.